Participation in the Science Fair: A call for data - Wehi, Priscilla; Anderson, Barbara; Haines, Esther (New Zealand Science Review, 2014)
​There are many reasons to encourage diverse participation in science (Westminster Business School 2014). Importantly, the recruitment and retention of talent for the scientific workforce needs to be socially inclusive to ensure we access the necessary talent. Scientific progress also benefits from the range of perspectives that arise from diverse, heterogeneous teams (Kandola & Fullerton 1998 in Westminster Business School 2014). Science is an increasingly collaborative activity, and current thinking suggests that a diverse workforce enables us to incorporate multiple perspectives to enhance creativity and innovation, while also ensuring that the outcomes of research are relevant and accessible to all groups. In addition, there is an underlying moral and social case for diversity in the scientific workforce (Westminster Business School 2014).